Environmental background values of trace elements in sediments from the Jiaozhou Bay catchment, Qingdao, China. Issue 1 (15th August 2017) - Xu, Fangjian; Liu, Zhaoqing; Yuan, Shengqiang; Zhang, Xilin; Sun, Zhilei; Xu, Feng; Jiang, Zuzhou; Li, Anchun; Yin, Xuebo
Abstract: Selected trace elements (As, Cr, Zn, Cu, Cd, Co, Pb and Ni) in 76 surface sediment samples collected from the rivers and the intertidal zone of Jiaozhou Bay (JZB) were evaluated to assess their environmental background values in the JZB catchment. Overall, the sediment quality in the area meets the China Marine Sediment Quality criteria. The background values (ranges) of the elements As, Cr, Zn, Cu, Cd, Co, Pb and Ni were, respectively, 8.28 (4.10–12.46), 67.96 (38.40–97.52), 56.80 (16.42–196.51), 19.13 (5.71–64.06), 0.10 (0.02–0.42), 6.51 (2.08–20.40), 17.97 (12.26–55.84) and 20.69 (10.43–30.95) mg/kg. The background values of most of the trace elements were lower than those in Chinese soil, the upper continental crust, global shales and global preindustrial sediments. The results may assist in defining future coastal and river management measures specifically targeted at monitoring trace element contamination in the JZB catchment. Highlights: Background values of trace elements in sediments from the Jiaozhou Bay catchment are reported. The sediments have relatively low levels of trace elements. The use of different background values leads to variations in the assessment results.